Temperature monitoring of various crop with and without seasonal extension techniques during the 2022 growing season in Fairbanks, Alaska ... - Ward Jones, Melissa; Gannon, Glenna; Jones, Benjamin (NSF Arctic Data Center, 2024)
The Permafrost Grown project (NSF RISE Award # 2126965) is co-producing knowledge with farmers in Alaska (Tanana Valley and Bethel) to investigate the interactions and feedbacks between permafrost and agriculture. Additional project objectives include understanding legacy effects over a 120-year cultivation history in the Tanana Valley, evaluating the socio-economic effects of permafrost-agriculture interactions and provide decision making tools for farmers and finally to utilize education and outreach activities to share knowledge with the farmers and the public. The project focuses on in-the-ground farming in a range of cultivation types including crops, peonies and livestock. The project is funded through the National Science Foundation's (NSF) Navigating the New Arctic Initiative. Temperature monitoring of various crop types with and without extension techniques was done at two farm sites in Fairbanks, Alaska (AK) during the 2022 growing season. This work was done through the Permafrost Grown Project as ...